Effect of sodium nitroprusside on germination of Trigonell foenum-graceum seeds under cadmium stress - Sharma, Deboja; Agarwala, Satyakam; Dkhar, Reshma; Mazumder, Tahmina (Journal of Postharvest Technology, 2022)
Fenugreek (Trigonell foenum-graceum) is one of the oldest cultivated medicinal plants whose seeds are been found to have higher mineral,  protein, carbohydrate content and antioxidant properties. Germination is one of the most important physiological events in a plant life cycle that  is well protected against various stresses. The most important factors limiting germination of matured seeds are various environmental stress  conditions like the presence of heavy metals in soil, lack of water etc. Metal poisoning affects the plant growth process, therefore, affecting crop  yield. Cadmium is one of the most reactive heavy metal contaminants and is the most vulnerable to accumulation. Thus, fenugreek being a  valuable medicinal plant demands further investigation into its response to cadmium-induced phytotoxicity during germination. The goal of this  study was to investigate the effect of sodium nitroprusside (SNP) on seeds treated with cadmium chloride during germination and its antioxidant  activity. SNP is known to donate nitric oxide that plays a pivotal role in seed germination and acts against oxidative stress. Phytochemical  analysis of about 25 fenugreek seeds was carried out using different strategies and methodologies. Estimation of antioxidant activity and effect  of SNP on CdCl₂treated seeds were evaluated. The phytotoxicity percentage remarkably increased with an increase in metal toxicity while seeds  treated with SNP showed increased protein concentration. Germination percentage however decreased with increasing metal toxicity. Proline  accumulation was found to be more in 200µM SNP and decreased with increasing SNP concentration. The scavenging activity of SNP-treated  seed exposed to CdCl₂was found to be significant.
Keywords: Cadmium stress; fenugreek; germination; phytotoxicity; sodium nitroprusside